Survey of Reserve Managers : Lessons from the Crisis - Morahan, Aideen (IMF Working Papers; Working Paper ;, 2013)
This paper reports in detail on a survey that was circulated to reserve managing central banks of IMF member countries in April 2012. The survey aims to gain further insight into how reserve managers have reacted to the crisis to date. The survey also aims to understand how reserve managers arrive at their strategic asset allocation and how they operate their risk management frameworks in practice. Some of the key themes that emerge from the survey include potential procyclical and counter cyclical behavior by reserve managers, increased focus placed on returns and wide variability across countries in how the currency composition of reserves is derived.